The Economics of Retirement Behavior - Mitchell, Olivia S.; Fields, Gary S. (Journal of Labor Economics, 1984)
This paper examines the role of economic factors in determining retirement behavior using a unique new data archive on more than 8,700 workers covered by 10 different pension plans. We build on our earlier work by estimating several different retirement models including both linear and discrete choice formulations. This framework provides new insights into how and why retirement ages differ across firms. We conclude that older workers' income opportunities differ depending on their pension rules, which in turn have a powerful influence on their retirement patterns. In addition, the models indicate that older workers' tastes for income are not uniform, either across individuals or across firms. Finally, we show that retirement age differences are due in part to differences in worker preferences and in part to differences in income opportunities. There appears to be some evidence of worker sorting across pension plans.